Department Of Management, Faculty Of Economics And Business, Unisa Palu Information Technology Towards The Effectiveness Process For Supply Chain Management - Idham, Idham; Adfar, Mohamad (International Journal of Science, Technology & Management, 2024)
Prove the effectiveness and efficiency of supply chain management through the application of a StartUp product. The methodology used in this research is a qualitative approach, namely through participatory observation, depending on experience, case studies and other literature related to measuring the effectiveness and efficiency of Supply Chain Management through the application of a StartUp product. It seeks to integrate work in supply chain management, by implementing a StartUp product into one partnership. Cooperation that results in effectiveness and efficiency in the scope of work. The findings obtained are effective ProductStartUp and efficiency of Supply Chain Management, namely by facilitating information, logistics, making references, strategies and reducing risks as well as reducing costs and reducing the risk of reducing complaints, and increasing satisfaction. This research provides many fields, where researchers can complete additional research and develop further research agendas. Originality value - This paper provides some insight into the effectiveness and efficiency of Supply Chain Management, focusing on facilitating information, logistics, making references, strategies and reducing risks while also reducing the cost of reducing complaints, and increasing satisfaction. towards supply chain management.